Lights and shades in the search with stem cells - Capella, Vincente Bellver (Medicina e Morale, 2000)
Great Britain has recently opened to the possibility to clone human embryos in the perspectives to get tissues to transplant in patient who need them. The United States, with the same purpose, intend to finance the search on the spare embryos obtained from reproductive technologies. In this article, sustained by the most recent available literature, the author thinks that least controversial from the ethical point of view ways to get the same therapeutic goals are available and reports the business that push to offer a partial information on this subject, besides a great deal remarkable for the medicine of the future.